2010
DOI: 10.5194/acp-10-547-2010
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl sulfide exchange in a temperate loblolly pine forest grown under ambient and elevated CO<sub>2</sub>

Abstract: Abstract. Vegetation, soil and ecosystem level carbonyl sulfide (COS) exchange was observed at Duke Forest, a temperate loblolly pine forest, grown under ambient (Ring 1, R1) and elevated (Ring 2, R2) CO 2 . During calm meteorological conditions, ambient COS mixing ratios at the top of the forest canopy followed a distinct diurnal pattern in both CO 2 growth regimes, with maximum COS mixing ratios during the day (R1=380±4 pptv and R2=373±3 pptv, daytime mean ± standard error) and minimums at night (R1=340±6 pp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 70 publications
2
29
1
Order By: Relevance
“…Interestingly, with the exception of beech in June/July and September/October 1999, a steady increase of V dCOS was found under 800 ppm CO 2 . Such a development of V dCOS is in accordance with data observed with sweetgum (White et al, 2010) but contrasts with the behavior of loblolly pine trees as reported by the same authors. However, we should have in mind that the third measurement period for the oak species was scheduled for a winter period, which limits a consistent interpretation.…”
Section: Leaf Conductances Deposition Velocities and Ca Activitiessupporting
confidence: 78%
“…Interestingly, with the exception of beech in June/July and September/October 1999, a steady increase of V dCOS was found under 800 ppm CO 2 . Such a development of V dCOS is in accordance with data observed with sweetgum (White et al, 2010) but contrasts with the behavior of loblolly pine trees as reported by the same authors. However, we should have in mind that the third measurement period for the oak species was scheduled for a winter period, which limits a consistent interpretation.…”
Section: Leaf Conductances Deposition Velocities and Ca Activitiessupporting
confidence: 78%
“…Several field studies provide support for this by showing that soils generally act as an OCS sink when measured at ambient concentrations (Castro and Galloway, 1991;Kuhn et al, 1999;J. Liu et al, 2010;Steinbacher et al, 2004;White et al, 2010;Yi et al, 2007) and that the uptake rate is reduced when the soil is autoclaved (Bremner and Banwart, 1976). Kesselmeier et al (1999) also observed a significant (> 50 %) reduction of the OCS uptake rate in soil samples after adding ethoxyzolamide, one of the most efficient known CA inhibitors (e.g.…”
Section: J Ogée Et Al: a New Mechanistic Framework To Predict Ocs Fmentioning
confidence: 89%
“…This means that vegetative uptake of COS can continue during the night if stomata are not completely closed . Caird et al (2007) showed that nighttime stomatal conductance exists in a wide variety of plant species and several studies report nighttime depletion of COS mole fractions (White et al, 2010;Belviso et al, 2013;Commane et al, 2013Commane et al, , 2015Berkelhammer et al, 2014;Maseyk et al, 2014;Wehr et al, 2017). The measurements presented in White et al (2010), Maseyk et al (2014), Berkelhammer et al (2014) and Wehr et al (2017) indicated that nighttime ecosystem COS fluxes were indeed dominated by the vegetation, and not by the soil.…”
Section: Introductionmentioning
confidence: 86%
“…The integral was determined from hourly measured profile concentrations at 0.5, 4, 14, and 23 m in two ways: (1) by integrating an exponential fit through the data, and (2) by using trapezoidal areas (Winderlich et al, 2014). The concentration at ground level that is used for the second calculation method is estimated by extrapolating the gradient between 0.5 and 4 m to the ground level.…”
Section: Storage Fluxesmentioning
confidence: 99%